Voriconazole-induced periostitis in a child with finger pain and nodules: case report and literature review - Hiroshi Urakawa; Kunihiro Ikuta; Tomohisa Sakai; Hiroshi Koike; Takeo Fujito; Yoshihiro Nishida; Shiro Imagama (BMC Musculoskeletal Disorders)
Abstract Background Voriconazole-induced periostitis is predominantly reported in adults, with pediatric cases being exceedingly rare. Case presentation This report describes an 8-year-old boy with voriconazole-induced periostitis presenting with finger pain and nodules, initially suspected to be bone tumors. The patient had been on voriconazole for two years and seven months to treat Aspergillus pneumonia and had been hospitalized for six months due to chronic graft-versus-host disease following hematopoietic stem cell transplantation and total body irradiation for severe congenital neutropenia. The patient presented with a five-month history of pain and a one-month history of a mass in the middle finger of his right hand. Radiographs revealed bone formation outside the cortical bone in the proximal phalanx of the right middle finger and the distal ulna. Differential diagnoses included benign bone-forming tumors, such as osteochondroma post-total body irradiation, and bizarre parosteal osteochondromatous proliferation. The diagnosis of voriconazole-induced periostitis was confirmed as new sites of periostitis became apparent during the disease course. Conclusions Voriconazole-induced periostitis should be considered, even in pediatric patients, when multiple nodular periosteal reactions are observed in immunosuppressed patients undergoing long-term voriconazole therapy.